The nanoencapsulation of curcuminoids extracted from Curcuma longa L. and an evaluation of their cytotoxic, enzymatic, antioxidant and anti-inflammatory activities. Issue 2 (29th January 2019) - dos Santos, Priscila Dayane Freitas; Francisco, Cristhian Rafael Lopes; Coqueiro, Aline; Leimann, Fernanda Vitória; Pinela, José; Calhelha, Ricardo C.; Porto Ineu, Rafael; Ferreira, Isabel C. F. R.; Bona, Evandro; Gonçalves, Odinei Hess
Abstract : Curcumin, bisdemethoxycurcumin and demethoxycurcumin are known for their bioactivity. Abstract : Curcumin, bisdemethoxycurcumin and demethoxycurcumin are the main curcuminoids present in Curcuma longa L. and are known for their bioactivity. However, their low water solubility results in poor bioavailability and therapeutic efficacy. This work aimed to investigate the in vitro modulation capacity on the enzymes acetylcholinesterase (AChE) and glutathione S -transferase (GST), as well as the in vitro antioxidant (OxHLIA and TBARS) and anti-inflammatory activities (RAW 264.7 test) of nanoencapsulated curcuminoids. Cytotoxicity on tumor and non-tumor cell lines was also investigated. Curcuminoid nanoparticles significantly inhibited the in vitro activity of AChE (12% inhibition at 50 μM) and GST (30% inhibition at 5 μM). They presented antioxidant activity and toxic effects against breast adenocarcinoma, lung, cervical and hepatocellular carcinoma cells when dispersed in water. Encapsulated curcuminoids exhibited bioactive properties in aqueous medium (no hydrophobic solvent added), exerting antioxidant and cytotoxic effects and acting on the cholinergic and endogenous antioxidant systems.